2016
DOI: 10.7554/elife.18249
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric activation of SENP1 by SUMO1 β-grasp domain involves a dock-and-coalesce mechanism

Abstract: Small ubiquitin-related modifiers (SUMOs) are conjugated to proteins to regulate a variety of cellular processes. SENPs are cysteine proteases with a catalytic center located within a channel between two subdomains that catalyzes SUMO C-terminal cleavage for processing of SUMO precursors and de-SUMOylation of target proteins. The β-grasp domain of SUMOs binds to an exosite cleft, and allosterically activates SENPs via an unknown mechanism. Our molecular dynamics simulations showed that binding of the β-grasp d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
(64 reference statements)
1
16
0
Order By: Relevance
“…Overall, local quenching of subdomain dynamics in the MD and CTD regions of Hsp90 can be counterbalanced by strengthening of the inter-domain correlations and inter-molecular couplings. A similar pattern of dynamic changes induced by allosteric activators was detected in other protein systems that are primarily regulated by dynamically-driven allostery [ 103 105 ].…”
Section: Resultssupporting
confidence: 61%
“…Overall, local quenching of subdomain dynamics in the MD and CTD regions of Hsp90 can be counterbalanced by strengthening of the inter-domain correlations and inter-molecular couplings. A similar pattern of dynamic changes induced by allosteric activators was detected in other protein systems that are primarily regulated by dynamically-driven allostery [ 103 105 ].…”
Section: Resultssupporting
confidence: 61%
“…Rogers et al (65) recently presented a scenario of dock and coalesce, with the docking and coalescing segments identified by experimental data for the effects of point mutations within the binding site on the binding rate constant. Interestingly, in addition to direct interactions within the binding site, allosteric effects by distally bound domains may also facilitate the dock-and-coalesce mechanism (33). …”
Section: Determination and Determinants Of Binding Mechanismsmentioning
confidence: 99%
“…We measured the distances between these key residues in these structures and found that neither Y270F nor Y270E mutation brought obvious changes to it (Figure 6B). Since the binding of SUMO1 β-grasp domain (residues 20-92) induces structural changes in the active site of SENP1 and then enhances the enzyme activity of SENP1 (Chen et al, 2014;Guo and Zhou, 2016), the binding of SUMO to SENP1 is hence a prerequisite for SENP1 isopeptidase activity, and we wondered whether Y270 phosphorylation on SENP1 could regulate its isopeptidase activity via modulating its binding to SUMO-conjugated substrates. We performed the GST pull-down assay by using GST fused to the N-terminus of mature SUMO1 (1-97 aa) or SUMO3 (1-92 aa).…”
Section: Senp1 Y270 Phosphorylation Influences Its Binding Propensity...mentioning
confidence: 99%